Relationships Among Personality, Situational Construal and Social Outcomes. Issue 2 (March 2015) - Morse, Patrick J.; Sauerberger, Kyle S.; Todd, Elysia; Funder, David
Abstract: The present study demonstrates a novel way of exploring the relationship between personality and social outcomes by examining an understudied intermediate step: situational construal. Construal is assessed in terms of the degree to which one's description of a situation agrees with others' descriptions of the same situation (normativity) and the degree to which the description is positively valenced. Participants (N = 256) provided information about their personality and subsequently used the Riverside Situational Q‐sort to describe their construal of three in‐lab interactions with unacquainted others. A measure of positive behavioural social outcomes was constructed from observer ratings of the video‐recorded interactions. Extraversion, agreeableness, openness and neuroticism (negatively) were related to positive behavioural social outcomes, as well as to normativity and positivity of construal. Additionally, normativity and positivity of construal were related to positive social outcomes. However, mediation analyses did not confirm that construal mediates the relation between personality and positive social outcomes. Copyright © 2015 European Association of Personality Psychology